A randomized clinical split-mouth trial of a bulk-fill and a nanohybrid composite restorative in class II cavities: three-year results - Sekundo, Caroline; Fazeli, Shila Marlen; Felten, Anna; Schoilew, Kyrill; Wolff, Diana; Frese, Cornelia (Dental materials, 2022)
Objectives - The aim of this randomized controlled clinical trial was to evaluate the clinical survival and quality parameters of class-II restorations using a bulk-fill composite resin compared to a conventional nanohybrid composite resin in a split-mouth design. - Methods - One hundred and twenty direct restorations were placed in stress bearing class II cavities (n = 60 test group: Filtek™ Bulk Fill Posterior and n = 60 control group: Filtek™ Supreme XTE) in adult permanent teeth. Survival and clinical quality were evaluated at baseline and after 3 years using modified World Dental Federation (FDI) criteria. Participants and clinical evaluators were blinded relating to the group assignment of the restorations. - Results - Seventeen restorations (14.2%) were lost to follow-up, leading to 51 restorations available for survival analysis in the test group and 52 restorations in the control group. Seven restorations showed unfavorable events and were classified as failure. Four bulk-fill restorations failed due to tooth infracture (n = 1), chipping fractures (n = 2) and recurrent decay (n = 1), whereas three conventional nanohybrid composite restorations failed due to adhesive failure (n = 1), tooth infracture (n = 1) and chipping as well as recurrent decay (n = 1). The mean annual failure rate was 2.4% and 1.8%, respectively. The difference between test and control group was not significant (p = 0.7). Data on the detailed assessment of FDI criteria were available for n = 48 and n = 49 restorations, respectively. No significant differences between the two groups could be found regarding the assessment of esthetic, functional and biological properties. - Significance - Both materials showed similar clinical performance and survival. The use of bulk-fill composite proved to be an esthetically, functionally and biologically satisfactory alternative in the posterior dentition during the 3-year follow-up.
Gesehen am 29.06.2022